2012
DOI: 10.1152/ajpgi.00499.2011
|View full text |Cite
|
Sign up to set email alerts
|

Platelets orchestrate remote tissue damage after mesenteric ischemia-reperfusion

Abstract: Ischemia-reperfusion (I/R) injury is a leading cause of morbidity and mortality. A functional role for platelets in tissue damage after mesenteric I/R is largely unknown. The hypothesis that mesenteric I/R local and remote injury are platelet dependent was tested. Using a murine mesenteric I/R model, we demonstrate that platelets orchestrate remote lung tissue damage that follows mesenteric I/R injury and also contribute, albeit to a lesser degree, to local villi damage. While lung damage is delayed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 83 publications
2
26
1
1
Order By: Relevance
“…Consequently, the resulting microvascular plugging with leukocytes and activated platelets may be pivotal in the pathogenesis of postoperative AKI, 12 similarly as it has been observed in sepsis-induced kidney injury. In addition, recent evidence supports the role of platelets as potent and ubiquitously present sources of inflammatory activation, 13,14 in defining endothelial responses and neutrophil recruitment in ischemia/reperfusion injury including distant organ injury 15 and postischemic renal failure. 16 …”
Section: Introductionmentioning
confidence: 93%
“…Consequently, the resulting microvascular plugging with leukocytes and activated platelets may be pivotal in the pathogenesis of postoperative AKI, 12 similarly as it has been observed in sepsis-induced kidney injury. In addition, recent evidence supports the role of platelets as potent and ubiquitously present sources of inflammatory activation, 13,14 in defining endothelial responses and neutrophil recruitment in ischemia/reperfusion injury including distant organ injury 15 and postischemic renal failure. 16 …”
Section: Introductionmentioning
confidence: 93%
“…It is not clear how natural Ig interacts with platelets or whether this interaction may be, in part, responsible for perpetuation of local or initiation of remote tissue damage following mesenteric I/R. However, our laboratory previously demonstrated that platelets may only indirectly participate in intestinal injury, but are central for the development of remote lung injury (31,32). Our group has also demonstrated increased deposition of IgM and IgA in intestine and lung after mesenteric I/R (31,49).…”
Section: Discussionmentioning
confidence: 89%
“…Platelet numbers were adjusted to 2 ϫ 10 9 /ml after counting with the Hemavet 850 (Drew Scientific, Farmington, CT), and the final volume was adjusted to 200 l for the platelet transfusion protocol. Platelets were transfused into plateletdepleted mice 10 min before the initiation of I/R injury, as described previously (20,31,32). In platelet-depleted mice, one group received platelets containing inactive Syk (treated with the Syk inhibitor, R788), and the other received normal platelets.…”
Section: Methodsmentioning
confidence: 99%
“…After mesenteric IRI, platelets lodge at increasing amounts over 24 hours in the lungs and they appear to be covered with complement. 7 Although we do not know if complement deposition causes or facilitates platelet activation, it is certain that the deposited complement may facilitate remote lodging, whereas peptidoglycan activates them and causes thrombus formation. In that respect, the scFv-Crry construct prevents complement activation at the site of injury and, by not altering immunity to bacteria, limits the possibility for MDP-mediated platelet activation.…”
Section: March 31 2015mentioning
confidence: 99%